Mathematical Modelling in Cyber Security and Cyber Defense (Trinity Journal of Management, IT & Media (TJMITM), 2023)
Cybersecurity is a technical field and one that at its core, requires strong quantitative  skills. This paper is all about how mathematics is used in cybersecurity. Most  cybersecurity studies generally require basic mathematics concepts that are used  in binary, cryptography, or some minimal programming tasks.This paper gives an introduction to a realistic problem of current cyberspace i.e.  cyber-attacks and defense. Description of the objects used for cyber-attacks and  tell the means of spreading them such as secondary memory, e-mail attachments,  instant messages or malicious bots. Roll of mathematical modeling and simulation  to solve the problem with an extensive literature review. A cyber defense  architecture and possible elements of cyber defense model are also studied for  finding the research gaps. After surveying a wide range of cyber security issues, I come to the conclusion  that the field of cyber security gives rise to a rich set of new and exciting research  opportunities for the mathematical and statistical techniques.
Keywords: Cybersecurity; Cryptographic methods; Data and information security; mathematical modeling; Network security; Privacy and anonymity; Software safety; System security